2015
DOI: 10.1186/s12870-015-0437-1
|View full text |Cite
|
Sign up to set email alerts
|

The contrasting N management of two oilseed rape genotypes reveals the mechanisms of proteolysis associated with leaf N remobilization and the respective contributions of leaves and stems to N storage and remobilization during seed filling

Abstract: BackgroundOilseed rape is the third largest oleaginous crop in the world but requires high levels of N fertilizer of which only 50% is recovered in seeds. This weak N use efficiency is associated with a low foliar N remobilization, leading to a significant return of N to the soil and a risk of pollution. Contrary to what is observed during senescence in the vegetative stages, N remobilization from stems and leaves is considered efficient during monocarpic senescence. However, the contribution of stems towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 72 publications
5
66
0
1
Order By: Relevance
“…Unlike cereals, which have a long history of domestication, oilseed rape (Brassica napus) and Arabidopsis still show considerable variation in N remobilization efficiency across related populations (Chardon et al, 2014;Girondé et al, 2015). Moreover, in many Brassica spp.…”
Section: Carbon-nitrogen Resource Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike cereals, which have a long history of domestication, oilseed rape (Brassica napus) and Arabidopsis still show considerable variation in N remobilization efficiency across related populations (Chardon et al, 2014;Girondé et al, 2015). Moreover, in many Brassica spp.…”
Section: Carbon-nitrogen Resource Allocationmentioning
confidence: 99%
“…The salvaging of the chloroplasts allows a major portion of leaf lipids and proteins to be recycled (Ischebeck et al, 2006). As chloroplasts contain the majority of leaf proteins, they represent a rich source of nitrogen (N), and their salvaging provides up to 80% of the final N content of grains (Girondé et al, 2015).…”
mentioning
confidence: 99%
“…In rapeseed, the stems have been described as N-storage buffer organs that could improve this synchronization (Hocking et al 1997;Rossato et al 2001;Malagoli et al 2005a). According to Girondé et al (2015), a high amount of N in the stems at the beginning of the reproductive stage, and better N remobilization from the stems to the seeds, are characteristic features of high nitrogen remobilization efficiency. There is evidence for genetic variation in N stem remobilization in rapeseed (Berry et al 2010;Girondé et al 2015), but that variation is not always correlated with nitrogen utilization efficiency under low N supply.…”
Section: Nitrogen Remobilization Efficiency In Rapeseedmentioning
confidence: 99%
“…According to Girondé et al (2015), a high amount of N in the stems at the beginning of the reproductive stage, and better N remobilization from the stems to the seeds, are characteristic features of high nitrogen remobilization efficiency. There is evidence for genetic variation in N stem remobilization in rapeseed (Berry et al 2010;Girondé et al 2015), but that variation is not always correlated with nitrogen utilization efficiency under low N supply. This finding was confirmed by data from diverse winter rapeseed accessions grown under low and high N fertilization, where the N content in the stems at flowering was not significantly related to nitrogen utilization efficiency (Fig.…”
Section: Nitrogen Remobilization Efficiency In Rapeseedmentioning
confidence: 99%
“…Cai et al (1995) investigated the rapeseed nitrogen recovery efficiency by 15 N labelling technique and reported that rapeseed plant recovery efficiency of nitrogen as basal and topdressing at the flowering stage was 44.0% and 33.4% of the applied N, respectively. Meanwhile, many researchers maintained that the apparent N transport efficiency of rapeseed grain was about 41.0~65.0% from vegetative tissues, and the transport capacity was obviously higher under moderate nitrogen stress conditions than under normal or severe nitrogen stress conditions, with the apparent N transport efficiency of rapeseed grain being roughly 70-94% (Hocking et al, 1997;Rossato et al, 2001;Malagoli et al, 2005;Gombert et al, 2010;Franzaring et al, 2012;Gironde et al, 2015a). However, there have been few reports available on the use efficiency of nitrogen fertilizer as basal and topdressing in different organs of rapeseed and the residual N recovery efficiency by the subsequent crop.…”
mentioning
confidence: 99%